2018
DOI: 10.3390/v10120679
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism Underlying Attenuation of Recombinant Influenza A Viruses Carrying Reporter Genes

Abstract: Influenza A viruses (IAV) carrying reporter genes provide a powerful tool to study viral infection and pathogenesis in vivo, however, incorporating a non-essential gene into the IAV genome often results in virus attenuation and genetic instability. Very few studies have systematically compared different reporter IAVs, and most optimization attempts seem to lack authentic directions. In this study, we evaluated the ratio of genome copies to the number of infectious unit of two reporter IAVs, PR8-NS1-Gluc and PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…In the present study, the strategy of fusing reporter genes to the NS1 open reading frame that was successfully used to construct reporter influenza A subtype H1N1 viruses [28,45] failed to generate a reporter influenza A subtype H3N2 virus (Figure 1). This is not surprising, since our previous study demonstrated that the vRNA replication of an IAV segment can be impaired by the insertion of exogenous genes, resulting in an imbalance of the eight segments during genome replication [33]. We speculate that the NS segment of IAV H3N2 is more vulnerable than that of H1N1 to the modification.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In the present study, the strategy of fusing reporter genes to the NS1 open reading frame that was successfully used to construct reporter influenza A subtype H1N1 viruses [28,45] failed to generate a reporter influenza A subtype H3N2 virus (Figure 1). This is not surprising, since our previous study demonstrated that the vRNA replication of an IAV segment can be impaired by the insertion of exogenous genes, resulting in an imbalance of the eight segments during genome replication [33]. We speculate that the NS segment of IAV H3N2 is more vulnerable than that of H1N1 to the modification.…”
Section: Discussionmentioning
confidence: 73%
“…The TCID 50 values were determined using MDCK cells and the titer was calculated by the Reed–Muench method [33].…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we generated a recombinant IAV expressing Gaussia luciferase, based on which a phenotypic high-throughput screening approach was subsequently established, providing a powerful tool for antiviral discovery [ 11 , 12 , 15 ]. A phenotypic screening was therefore carried out against the prefractionated TCM library for anti-influenza actives.…”
Section: Resultsmentioning
confidence: 99%
“…Madin–Darby canine kidney (MDCK) epithelial cells were grown in Dulbecco's modified Eagle's medium (DMEM; Cellgro, Manassas, VA, USA) supplemented with 10% fetal bovine serum (FBS; Gibco, Carlsbad, CA, USA), 1,000 units/mL penicillin and 100 μ g/mL of streptomycin (Invitrogen, Carlsbad, CA, USA). The replication-competent reporter influenza A virus carrying the Gaussia luciferase gene (PR8-PB2-Gluc) and wildtype influenza A/Puerto Rico/8/34 (H1N1, PR8) were propagated as previously described [ 11 , 12 , 15 ]. Infections were performed in Opti-MEM containing 1.5 µ g/mL N-tosyl-L-phenylalanine chloromethyl ketone (TPCK)-trypsin (Sigma-Aldrich, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Human embryonic kidney cell line 293T and Madin-Darby canine kidney (MDCK) epithelial cells were obtained from Dr. Fei Deng (Wuhan Institute of Virology, CAS, China) and grown in Dulbecco’s modified Eagle’s medium (DMEM; Cellgro, Manassas, VA, USA) supplemented with 10% fetal bovine serum (FBS; Gibco, Carlsbad, CA, USA), 1000 units/mL penicillin, and 100 μg/mL of streptomycin (Invitrogen, Carlsbad, CA, USA). The influenza A reporter PR8-Gluc virus and wild-type PR8 virus were generated and stocked in our lab as previously described [35].…”
Section: Methodsmentioning
confidence: 99%